SM-ND ISOTOPIC SYSTEMATICS OF ALKALINE ROCKS AND CARBONATITES FROM THE EDEL'VEIS COMPLEX, NORTHERN CHUYA RANGE, GORNYI ALTAI - Vrublevskii V.V.; Gertner I.F.; Rikhvanov L.P.; Zhuravlev D.Z.; Krupchatnikov V.I.; Vladimirov A.G. (My University, 2004)
The obtained isotopic data suggest the following conclusions: alkaline rocks and carbonatites of the Edel'veis Complex formed at the late collisional stage in the Middle Ordovician; the comagmatic association was derived from moderately depleted PREMA-type mantle; and evolution of derivative melts was complicated by crustal contamination, which was responsible for increase in Sr, O, and C isotopic ratios in rocks and minerals.